2016
DOI: 10.1186/s12886-016-0227-z
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thickness in obese women

Abstract: BackgroundExcessive weight is a well-known risk factor for microvascular diseases. Changes in thickness in a vascular tissue, such as the choroid, can be useful to evaluate the effect of obesity on the microvascular system. The aim of this study was to evaluate the choroidal thickness (CT) changes in obese women, using optical coherence tomography (OCT).MethodsThe prospective clinical study included examination of the right eyes of 72 patients. The right eyes of 68 patients were examined and served as the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
1
33
2
Order By: Relevance
“…Dogan et al have found that the subfoveal CT is significantly thinner in morbidly obese individuals compared to non-obese individuals [12]. In contrast, Yumusak et al have showed that a positive correlation is present between BMI and CT [13]. None of the our participants were obese.…”
Section: Dear Editorcontrasting
confidence: 79%
“…Dogan et al have found that the subfoveal CT is significantly thinner in morbidly obese individuals compared to non-obese individuals [12]. In contrast, Yumusak et al have showed that a positive correlation is present between BMI and CT [13]. None of the our participants were obese.…”
Section: Dear Editorcontrasting
confidence: 79%
“…Yilmaz et al also found negative correlations of between CT and both BMI and weight (26) . However, Yumusak et al (31) reported a positive correlation between BMI and CT in class two obese women, suggest that factors such as sex and severity of obesity may influence the relationship between BMI and choroidal blood flow.…”
Section: Discussionmentioning
confidence: 98%
“…High BMI values have been reported to cause retinal dysfunction by affecting the retinal vascular structure. 18 Furthermore, the relationship between obesity and ARM has been reported in many studies. 5,19 In the literature, it was reported that this relationship may be due to the systemic oxidative stress developed secondary to hyperleptinemia caused by obesity.…”
Section: Discussionmentioning
confidence: 99%
“…17 Obesity, a multifactorial condition, is one of the well-known causes of microvascular diseases and the basis of this relationship can be revealed by examining vascular tissue. 18 An examination of this relationship is also important in terms of determining the ocular effects of obesity, which has not been fully understood yet.…”
Section: Discussionmentioning
confidence: 99%